Joan Robinson y John Eatwell. Introduction to modern economics. Londres : McGraw Hill, 1974. 349 p. - Méndez Villarreal, Sofía (Estudios Demográficos y Urbanos, 1974)
JOAN ROBINSON y JOHN EATWELL, Introduction to Modern Economics, Londres, McGraw Hill, 1974.